Racism and Sexism, Together, in Counselling: Three Women of Colour Tell Their Stories - Gerrard, Nikki (Canadian Journal of Counselling and Psychotherapy, 2011)
Ten women of colour were interviewed for qualitative research about their experiences as clients in mental health systems. Of these, three stories are used here as examples. Preceding the stories, the terms "racism," "sexism," and "mental health systems" are defined. The dilemma of a white researcher doing research on women of colour presents moral, ethical, and political concerns. The ten women's paradigms of racism and sexism are summarized. The stories and the impact that the experiences had on the women are discussed. Suggestions for counselling research, theory, and practice include addressing racism within ourselves and with women of colour clients, and making space for women of colour in the centre of counseling work.